Benchmarking Chemical Stability of Arbitrarily Mixed 3D Hybrid Halide Perovskites for Solar Cell Applications. Issue 10 (14th August 2018) - García‐Fernández, Alberto; Juarez‐Perez, Emilio J.; Castro‐García, Socorro; Sánchez‐Andújar, Manuel; Ono, Luis K.; Jiang, Yan; Qi, Yabing
Abstract: Accurate and fast assessment of the intrinsic instability of mixed composition hybrid halide perovskite material is of vital importance for the development of perovskite solar cells. A longer lifetime close to current silicon‐based technology is a mandatory property for perovskite solar cells to reach commercial applications. The conventional method to evaluate the operational stability performance of perovskite solar cells relies on tracking maximum power efficiency on devices. However, this operational stability testing procedure requires a long measurement time, which is an inefficient procedure to screen the huge compositional space of mixed perovskites. Here, a thermal degradation protocol is shown for fast preliminary screening evaluation of the stability of any mixed 3D hybrid perovskite material. This stability assessment determines two independent parameters for stability quantification; 1) degradation temperature and 2) heat absorbed during degradation. Experimental entropic‐like parameter can be derived addressing the relative stability for each mixed hybrid perovskite composition. In addition, a first‐principle theoretical approach is described for the in silico search of optimal mixed composition perovskites. This experimental stability benchmarking protocol is able to signify several general rules of thumb to find enhanced stability trends in mixed composition perovskites prior to device assembly and conventional stability tests. Abstract : Mixed hybrid perovskites are a demonstrated winning strategy improving the operational stability of perovskite solar cells. However, the vast compositional space available could be impractical to explore exhaustively without adequate prescreening tools. Here, an experimental protocol to establish relative intrinsic chemical stability in arbitrarily mixed hybrid perovskites is shown to assist in the search for highly stable perovskite mixed compositions.